Data on hydrocarbons in sediment samples, and its body burden levels in tissues of Anomalocardia flexuosa from toxicity testing - Moreira, Lucas Buruaem [UNESP]; Sasaki, Silvio Tarou; Taniguchi, Satie; Figueira, Rubens Cesar Lopes; Bícego, Márcia Caruso; Costa-Lotufo, Leticia Veras; Abessa, Denis Moledo Souza [UNESP] (Elsevier, 2020)
The analysis of hydrocarbons in terms of individual compounds is relevant to understand the origin and source of these substances, as well as its distribution in environmental compartments, including sediments and biota. Hydrocarbons concentrations were determined in sediments and in whole-body soft tissues of the tropical clam Anomalocardia flexuosa in sediment toxicity testing using samples of Mucuripe bay (Ceará State, NE Brazil) collected in 2011 during dredging events [1]. Data of target compounds included aliphatic (AHs) and aromatic hydrocarbons (PAHs), and linear alkylbenzenes (LABs). AHs compounds were determined on gas chromatography with flame ionization detector (GC-FID), while PAHs and LABs were determined on gas chromatography coupled to a mass spectrometer (GC/MS) in a selected ion mode (SIM). The potential of this dataset is baseline information on hydrocarbons contamination in sediments from a semi-arid region and the bioaccumulation of organic contaminants in marine organisms that can be used as models in ecotoxicological studies.
Keywords: Bioaccumulation; Environmental monitoring; Linear alkylbenzenes; Marine pollution; Polycyclic aromatic hydrocarbons; Sublethal effects; Toxicity testing; Tropical environments